2021
DOI: 10.3390/fermentation7040317
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus oryzae Grown on Rice Hulls Used as an Additive for Pretreatment of Starch-Containing Wastewater from the Pulp and Paper Industry

Abstract: From an industrial point of view, the use of microorganisms as a wastewater bioremediation practice represents a sustainable and economic alternative for conventional treatments. In this work, we investigated the starch bioremediation of paper mill wastewater (PMW) with Aspergillus oryzae. This amylase-producing fungus was tested in submerged fermentation technology (SmF) and solid-state fermentation (SSF) on rice hulls. The tests were conducted to assay the concentration of the reducing sugars on paper mill w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A strain of Aspergillus oryzae that is safe to use and widely used in the brewing [1,2], enzyme [3,4], and waste treatment [5,6] industries is photoresponsive to different light wavelengths and intensities [7][8][9][10]. Our earlier investigation demonstrated that A. oryzae GDMCC 3.31 is more sensitive to CBL (475 nm) than to red light (630 nm) [11].…”
Section: Introductionmentioning
confidence: 96%
“…A strain of Aspergillus oryzae that is safe to use and widely used in the brewing [1,2], enzyme [3,4], and waste treatment [5,6] industries is photoresponsive to different light wavelengths and intensities [7][8][9][10]. Our earlier investigation demonstrated that A. oryzae GDMCC 3.31 is more sensitive to CBL (475 nm) than to red light (630 nm) [11].…”
Section: Introductionmentioning
confidence: 96%
“…For the synthesis of the ibuprofen esters, we decided to embark on the path of chemical modifications mediated by pathways with biological origins, also called biotransformation. These biochemical transformations can be achieved by exploiting whole cells (bacteria [18] or fungi [19]), their lysate, or isolated enzymes [20]. The latter allows for the synthesis of prodrugs through straightforward synthetic pathways, characterized as cheaper, less energy-consuming, and more selective compared to the canonical chemical modifications.…”
Section: Introductionmentioning
confidence: 99%